Collaborative Governance In Handling Urban Social Conflict: A Case Study Of The Role Of The Jakarta Provincial Government In The Manggarai Area - Muhamad Sirod; Nefra Firdaus; Anang Puji Utama; Panji Suwarno; Arifuddin Uksan (International Journal of Social Science, 2026)
The development of chronic urban social conflict in dense metropolitan areas, such as recurring youth group brawls in the Manggarai area of South Jakarta, presents a persistent challenge for local governance. Although the Jakarta Provincial Government and community leaders have jointly developed a multi-actor response to this conflict, the application of collaborative governance theory to this domain remains rarely examined, as the existing literature on conflict within collaborative governance is dominated by environmental and natural-resource contexts. This study aims to analyze the causes of recurring social conflict in Manggarai and to map how collaborative governance is enacted by the Jakarta Provincial Government together with community leaders in preventing, handling, and recovering from this conflict. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews with ten purposively selected informants from government, law enforcement, the Community Early Warning Forum (FKDM), and community elements, supplemented by field observation, documentation, and secondary statistical data. The findings indicate that recurring conflict in Manggarai is rooted in structural, social, and cultural antecedents, and that collaborative governance is institutionalized through Kesbangpol and FKDM and enacted through preventive, repressive, and rehabilitative stages, resulting in reduced conflict intensity despite persisting constraints. This study extends the Collaborative Governance Regime framework into the domain of urban social conflict and proposes a contextualized model relevant to strengthening social resilience and regional security.